Industry 4.0: is Portugal ready to change? - Mendes, Maria Beatriz Grilo (2021)
The world stands on the threshold of the fourth industrial revolution, also known as Industry 4.0. Having started in Germany, it rapidly gained a lot of attention and, although there is still no agreed definition, it is expected to radically transform businesses by merging virtual and physical worlds. This thesis uses a grounded theory methodology to analyze the data obtained in 9 interviews with experts, with the aim of identifying the adoption rate of Industry 4.0 in Portugal and understanding what are the factors influencing it. Five recommendations are proposed to increase the adoption and lead Portugal into the fourth revolution direction.